Sofia the first : magical story - Hapka, Catherine; Rothschild, Erica (England : Parragon Books, 2013)
Amber is planning a perfect princess slumber party. Sofia can't wait, but she's worried that her old friends from the village won't get along with her new royal friends.
K-3.
Keywords: Princess -- Fiction